Світова культура у творчій та епістолярній спадщині Т. Шевченка - Шацький, І.В. (Культура народов Причерноморья, 2014)
У статті досліджується питання взаємозв’язків європейської і української культурної
традицій на матеріалі художньої та епістолярної спадщини Т. Шевченка. Осягаються необхідність
звернення Т. Шевченка до постатей і художньої спадщини митців світової культури і літератури,
використання ремінісценцій зі світового культурного надбання людства, їх функції у творах
українського митця. В статье исследуется вопрос взаимосвязей европейской и украинской культурной
традиции на материале художественного и эпистолярного наследия Т. Шевченко. Осмысливаются
необходимость обращения Т. Шевченко к фигурам и художественному наследию авторов мировой
культуры и литературы, использования реминисценций из мирового культурного достояния
человечества, их функции в произведениях украинского писателя. In article the question of interrelations of the European and Ukrainian cultural traditions are
investigated on material of art and epistolary heritage of T. Shevchenko. Interrelations of the Ukrainian
literature with literatures of other peoples are one of the most actual problems of literary criticism.
Even the more actual is such research, when it deals with the artist whose creativity grew up on the richest soil
not only of Ukrainian, but also of all Slavic folklore and literary as well as West European cultural traditions. In
the Soviet literary criticism the thesis of the big dependence of T. Shevchenko’s creativity on the Russian cultural
influences was actively spread. Such statements are caused by the general statement of the idea that the
development of the Ukrainian literature in general is impossible separately from the Russian one. But
Shevchenko as the highly educated person of the time was perfectly familiar with the best achievements of world
cultural and literary thought that anyway couldn't but be reflected in art works of the artist.
The list of names, we find in works of the artist, testifies not only about his broad knowledge of the world
literature, but also about his great interest in various branches of art, science and culture.
The list of names that Shevchenko mentioned in his own art and epistolary heritage testifies to his broad
knowledge of the world literature and art. Knowledge of the outstanding aesthetic culture, wide erudition,
aspiration to continual improvement, creative unrest united T. Shevchenko with world spiritual wealth. Brought
up in a force field of the European romantic culture, he brought the individual type of the romantic mainly
creative system marked by the syncretism of styles, natural realness of perception in the world literature.
From Shevchenko's works the unique bright national image of Ukraine and an image of the outstanding artist
that became a symbolic embodiment of the Ukrainian and his mentality appeared to the European reader.